Microsoft office 2010 digital classroom - The AGI Training Team (Indianapolis,IN : Wiley, 2011)
Introduces Offices 2010, discussing the capabilities and new features of its programs, including Excel, Outlook, Word, PowerPoint, Access, OneNote, and Publisher.
"A complete training package!"--Cover
"Tutorials and lesson files on digitalclasroombooks.com"--Cover
Includes index
Keywords: Business -- Computer software; Microsoft Office; Microsoft Office (Computer software)